OVARIAN STEROIDAL PROFILE AND FERTILITY TO INSULIN AND GnRH ADMINISTRATION IN POSTPARTUM ANESTRUS BUFFALOES - V K, GUPTA; SHUKLA, S N; THAKUR, M S; AGRAWAL, R (The Indian Journal of Animal Reproduction, 2011)
To study the effect of exogenous administration of insulin on ovarian and fertility response in anestrusbuffaloes, 18 true anestrus buffaloes were selected and equally divided into 3- groups (n=6). Animals of group-I(G1) received subcutaneous injection of highly purified long acting bovine insulin at the dose of 0.25 I U kg-1bodyweight, once daily for 5 consecutive days. Animals of group~II (G2) received an intramuscular injection of 20μg buserelin acetate where as animals of group-Ill (control) received an intramuscular injection of 2.5 ml sterilesaline. In response to the treatment, 50 and 33.33% animals were induced in estrus with in 25 ± 0.94 and 9.5±3.18days from start of treatment, respectively in G1 and G2; however, no animal was induced in estrus in control group.Conception rate at induced estrus was 100% in both the treatment groups. The mean serum progesterone (P 4)concentration was less than 1 ng/ml on day before start of treatment, day 71h and 14111 following start of treatment inall the experimental animals. The basal level of P 4 concentration (nglml) at induced estrus (0.44 ±0.25 and 0.190.04) increased (4.46 ± 0.22 and 4.4 7 ± 0.58) significantly (p
Keywords: Insulin; anoestrus; fertility; Buffalo; GnRH